PENDIDIKAN KESEHATAN DETEKSI DINI ANEMIA PADA REMAJA SMP SEBAGAI UPAYA PENCEGAHAN ANEMIA - Karmilah; Jamalullai; Gerilona Maulina; Najwa Khusnul Khotimah; Ai Kurnia; Susanti; Imbaraniati Permana Putri; Delli Yuliana Rahmat (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Anemia in adolescents is a common health problem, especially in developing countries. The impact of anemia extends beyond the body and impacts a person's productivity and quality of life. Anemia can have a major negative impact on development, both physical and cognitive, academic achievement, and quality of life. Implementation of health education activities uses the lecture method using PowerPoint media and leaflet media prepared by the health education activities team. This health education aims to increase children's awareness of detecting anemia early so that they can recognize anemia early and of course, can prevent anemia from an early age. The results of this study indicate that there is a significant difference in anemia knowledge between before and after health education. Keywords: Adolescents, Anemia, Health Education,